2017
DOI: 10.4012/dmj.2016-064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy and precision of four intraoral scanners with 70% reduced inlay and four-unit bridge models of international standard

Abstract: The aims of this study were to evaluate the feasibility of 70% reduced inlay and 4-unit bridge models of International Standard (ISO 12836) assessing the accuracy of laboratory scanners to measure the accuracy of intraoral scanner. Four intraoral scanners (CS3500, Trios, Omnicam, and Bluecam) and one laboratory scanner (Ceramill MAP400) were used in this study. The height, depth, length, and angle of the models were measured from thirty scanned stereolithography (STL) images. There were no statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
1
29
1
2
Order By: Relevance
“…This study showed a significant difference in the accuracy according to the anterior and posterior regions in all eight scanners ( Table 2). Previous studies showed a difference in the accuracy according to the size and shape of the object scanned [2,19]. The accuracy was found to be poor in the posterior region in this study, suggesting that the manufacturer should improve this.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This study showed a significant difference in the accuracy according to the anterior and posterior regions in all eight scanners ( Table 2). Previous studies showed a difference in the accuracy according to the size and shape of the object scanned [2,19]. The accuracy was found to be poor in the posterior region in this study, suggesting that the manufacturer should improve this.…”
Section: Discussioncontrasting
confidence: 46%
“…The accuracy of intraoral scanners for a complete arch has been evaluated in many previous studies [3,8,10,[13][14][15][17][18][19]. It was found that the larger the range of scanning, the greater the error, suggesting that the complete arch was inappropriate as the range of intraoral scanning for prosthetic treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of dentists are purchasing and implementing intraoral scanners (IOS) for making optical impressions of oral soft and hard tissues as an alternative to traditional impressions, which are generally poorly tolerated by patients [1][2][3]. The area of application previously consisted mostly of quadrant imaging [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aimed to analyze and evaluate milling errors according to the types of ceramics through qualitative and quantitative analysis. A three-dimensional (3D) measuring program was used for the analysis, which is frequently adopted for measuring scanner errors and analyzing mechanical errors [ 26 , 27 , 28 ], in addition to assessing the accuracy of prostheses [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%